Learning Objectives in Older Adult Digital Education - Redefining Digital Inclusion - Łukasz Tomczyk; Natalia Edisherashvili (International Journal of Cognitive Research in Science, Engineering and Education)
The article explores the redefinition of learning objectives within the context of digital education for older adults, addressing the critical need to enhance digital inclusion. It emphasizes the centrality of learning objectives as foundational elements in the design, implementation, and evaluation of educational programs. The study underscores the necessity of revising these objectives to promote the development of digital competences among older adults. As society becomes increasingly digitalized, traditional educational models must evolve to accommodate the dynamic digital landscape. The REMEDIS research initiative seeks to modernize educational frameworks and establish a more effective approach to cultivating digital skills in older populations. By employing SMART criteria and leveraging the expertise of senior and future trainers, the study identifies 12 key categories for contemporary educational objectives, including: basic computer and mobile device use, digital terminology, email communication, cybersecurity, online information retrieval, social media usage, instant messaging, culture and entertainment access, online financial management, e-commerce, smartphone software applications, and time management. The qualitative analysis of digital education objectives for older adults reveals a spectrum ranging from basic digital literacy to advanced e-service utilization, while also highlighting the importance of aligning these objectives with the practical needs of older adults.